Effect of horizontal and radial airflow fans on the microclimate of single-span greenhouses and their yield - DUTTA, PRABHAT; AKPENPUUN, TIMOTHY DENEN; NA, WOOK-HO; OGUNLOWO, QAZEEM OPEYEMI; RABIU, ANIS; ADESANYA, MISBAUDEEN ADEREMI; OGUNDELE, OLUWASEGUN MOSES; ZAKIR, EZATULLAH; KIM, HYEON-TAE; LEE, Hyun-Woo (The Indian Journal of Agricultural Sciences, 2024)
The present study evaluated and compared the distribution patterns of microclimatic parameters within greenhouses to provide insights into optimizing growing conditions and maximizing crop productivity. Experiments were conducted from January to March 2023 at Sangju Smart Farm Innovation Valley, Sangju-si, South Korea, in two adjacent greenhouses covered with two polyolefin layers and a thermal screen layer. The distinctive design of the radial airflow fan connecting to the external environment and ability to uniformly blend air, demonstrated superior performance than the horizontal air flow fan. The adoption of radial airflow fans could greatly influence commercial production by enhancing the distribution of microclimate variables, resulting in improved greenhouse efficiency and ultimately leading to increased crop yields.